Pengaruh Jumlah Perusahaan Industri dan investasi terhadap Penyerapan Tenaga Kerja di Indonesia: Penelitian - Afriyani Elizabet Sitorus; Yesi Veronika Simarmata; Tasya Oren Sagala; Masyura Nasution; Khairani Alawiyah Matondang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the impact of the number of industrial enterprises and investment on labor absorption in Indonesia. Employment remains a critical issue, as the growth of the labor force has not been fully matched by sufficient job creation. The research uses annual secondary data obtained from the Central Bureau of Statistics (BPS) and relevant government reports. Multiple linear regression analysis was conducted using EViews software, with classical assumption tests applied to ensure the validity of the model. The findings reveal that both the number of industrial enterprises and investment have a positive and significant effect on labor absorption, both individually and jointly. The coefficient of determination (R²) of 98.08 percent indicates that the independent variables strongly explain variations in labor absorption. These results emphasize that expanding industrial enterprises and increasing investment are key drivers of job creation, and they imply that government policies should prioritize simplifying business establishment and promoting labor--intensive investment to achieve inclusive economic growth.